The outcome of the vein of Galen aneurysmal malformation cases diagnosed prenatally. (4th July 2022) - Turkyilmaz, Gurcan; Arisoy, Resul; Turkyilmaz, Sebnem; Erdogdu, Emre; Semiz, Altug
Abstract: Vein of Galen aneurysmal malformation (VGAM) is a rare foetal anomaly associated with neurodevelopment delay, cardiac failure, and even perinatal death. We aimed to assess prenatal features of VGAM and describe postnatal outcomes. This was a retrospective study involving six foetuses diagnosed with VGAM prenatally in two centres. All of the cases underwent foetal neurosonography and echocardiography. The presence of ventriculomegaly, intracranial haemorrhage and cardiac failure was recorded. Pregnancy and neonatal outcome information were obtained from medical records. The mean gestational age at diagnosis was 31.1 ± 5.1 weeks, and the mean size of VGAM was 29.2 ± 5.2 × 26.4 ± 3.3 mm. Ventriculomegaly was detected in five of six (83.3%) cases. Intracranial haemorrhage was present in five (83.3%) cases. Cardiac failure was shown in four (66.6%) foetuses. Three foetuses underwent termination of pregnancy (TOP); in two cases, neonatal death occurred. One patient was treated with endovascular embolisation, and there was no cardiac problem or neurodevelopment delay. Prenatally diagnosed VGAM have a poor prognosis, mainly if a cardiac failure or neurological consequences (intracranial haemorrhage, hydrocephaly) are present in utero . Impact Statement: What is already known on this subject? VGAM is the most common cerebral arteriovenous malformation detected prenatally, and it can lead to severe consequences in the perinatal period. What do the results of this study add? The accuracy of foetal neurosonography is excellent for detecting VGAM and associated brain abnormalities. Foetal echocardiography is mandatory for the prediction of prognosis What are the implications of these findings for clinical practice and/or further research? VGAM is associated with severe brain injury, cardiac failure, and the prognosis is generally poor. We need predictors to identify those expected to benefit from postnatal therapy.